Severe intestinal distension following HFNC-assisted awake intubation with conversion to open Nissen fundoplication: a case report - Zeynep Yasemin Tavşanoğlu; Ahmet Yüksek; Ali Sait Kavaklı; Ülkü Arslan; Mehmet Yılmaz (BMC Anesthesiology)
Abstract Background High-flow nasal cannula (HFNC) oxygen therapy is a commonly used respiratory support method delivering heated, humidified air at high flow rates with a positive end-expiratory pressure (PEEP) effect. HFNC improves oxygenation and facilitates awake fiberoptic intubation in the management of difficult airways. However, concerns about HFNC-induced gastric insufflation and intestinal distension have emerged, particularly in patients with lower esophageal sphincter dysfunction or hiatal hernia. We report a case of severe intestinal distension following HFNC-assisted awake fiberoptic intubation in a patient with a hiatal hernia scheduled for laparoscopic Nissen fundoplication. Case presentation A 50-year-old male patient was scheduled for a Nissen fundoplication procedure. Following preoperative airway examination, it was decided to proceed with awake intubation. HFNC was used as recommended in the guidelines to improve oxygenation. The patient was intubated with minimal sedation and airway topicalization under 40 L/min flow using a fiberoptic bronchoscope. The procedure was uneventful and the patient was handed over to the surgical team. Surgery began laparoscopically. However, excessive intestinal distension did not allow the surgery to continue with an optimum image. Aspirations with an orogastric tube and rectal tube could not improve the image and the patient had to undergo open surgery. The 5-hour open surgical procedure was completed without complications. Postoperative direct abdominal radiography showed dense intestinal air compared to the preoperative radiography. Conclusions This case underscores the potential risk of HFNC-induced intestinal distension, particularly in patients with predisposing factors such as hiatal hernia. Although HFNC is effective for airway management, careful patient selection and technique optimization are crucial. Further research is needed to clarify the impact of HFNC on gastrointestinal dynamics and to guide its safe application in at-risk populations.